Utilization off fermented copra meal with A. niger in broiler diet - Haryati, T; Togatorop, M.H; Sinurat, A.P; Purwadaria, T; ., Murtiyeni (Indonesian Animal Sciences Society, 2006)
Research of nutritional evaluation of fermented copra meal and its application in broiler has been conducted. In the first experiment the crude protein and fiber contents were determined in the fermented copra meal using A. niger BPT, NRRL 337 and ES1. Further, 384 of Indian River DOC were used for in vivo experiment. Completed Randomized Design was used with 8 treatments: Control without and with 10% addition of copra meal, 3 levels of fermented copra meal addition with Aspergillus niger BPT or A. niger NRRL 337 (10, 15, 20%). Every treatment was repeated 8 time with 6 birds each. Variables measured were body weight, consumption, feed conversion, mortalities and carcass analyses. Diets were formulated in isocalori and isoprotein. The research was conducted in 6 weeks. The results showed that fermentation process increased the copra meal protein content from 22.3 to 36.1; 35.6 and 38.6% respectively for fermentation with A. niger BPT, NRRL 337 and ES1, decreased the crude fiber from 19.5 to 13.0; 18.9 and 8.28%. Results during 3 weeks trial show that the treatment significantly affected on broiler performance (P<0.05). Fermented copra meal was better than non fermented copra meal. There was no significantly different (P>0.05) in broiler performance at 6 weeks trial evaluation. The best conversion was in diet with 10% fermented copra meal with A. niger BPT and NRRL 337. The feed conversion of diets with 10% of each fermented products were better than control or diet without copra meal. The feed conversion of 15% fermented copra meal addition was not significantly different to control. Utilization of fermented copra meal with A. niger BPT or NRRL 337 should not more than 15%. Key Words: Copra Meal, Bioprocess, Broiler